2016
DOI: 10.1002/adhm.201600808
|View full text |Cite
|
Sign up to set email alerts
|

Expanded 3D Nanofiber Scaffolds: Cell Penetration, Neovascularization, and Host Response

Abstract: Herein, we report a robust method to fabricate expanded nanofiber scaffolds with controlled size and thickness using a customized mold during the modified gas-foaming process. The expansion of nanofiber membranes was also simulated using a computational fluid model. Expanded nanofiber scaffolds implanted subcutaneously in rats showed cellular infiltration, whereas non-expanded scaffolds only had surface cellular attachment. Compared to unexpanded nanofiber scaffolds, more CD68+ and CD163+ cells were observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
134
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 37 publications
(50 reference statements)
2
134
0
Order By: Relevance
“…Electrospun nanofibrous scaffolds or nano/micro hybrid constructions have been demonstrated to promote cell adhesion, proliferation, and differentiation for tendon tissue engineering applications [2730]. However, such non-woven constructs also have several limitations that prevent broader clinical application [3133]. The tightly packed fibrous structure, small pore sizes existing between fibers (usually below 3 μm), and inferior controllability of fiber organization may limit cell growth, migration, and infiltration into the inner layers, and are not beneficial for the transportation of oxygen and nutrients throughout the implant site and removal of metabolic waste during tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun nanofibrous scaffolds or nano/micro hybrid constructions have been demonstrated to promote cell adhesion, proliferation, and differentiation for tendon tissue engineering applications [2730]. However, such non-woven constructs also have several limitations that prevent broader clinical application [3133]. The tightly packed fibrous structure, small pore sizes existing between fibers (usually below 3 μm), and inferior controllability of fiber organization may limit cell growth, migration, and infiltration into the inner layers, and are not beneficial for the transportation of oxygen and nutrients throughout the implant site and removal of metabolic waste during tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…4). [10,11] The nanofiber membrane was initially 0.4 mm thick and became about 4 mm thick after expansion. Figure 2 shows the morphology of a 3D nanofiber scaffold with arrayed holes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group has developed a modified gas-foaming technique to expand 2D nanofiber membranes in the third dimension with controlled thickness and highly porous structures. [10,11] It was also demonstrated that cells can infiltrate the expanded nanofiber scaffolds and proliferate within the nanofiber scaffolds. These promising results motivated us to fabricate a novel type nanofiber skin graft for chronic wound healing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations